Civil Service (special issue) (1991)
Eunan O'Halpin in his article deals with the relationship between civil servants and politicians in Ireland. The author concludes that Irish civil service has been extremely successful in elaborating and sustaining a profoundly a political ethos since 1922. John Stapleton discusses the emergence of civil service reform as a live policy issue on the agenda of Irish politics and Public administration. Sean cromien explains the role of the Department of finance in Controlling Public expenditure in Ireland which helps in maintaining balance in the states's finances and thereby contributes to the development of economy. Tom O'Connor in his article describes some special features of Civil Service, examines the, , Civil Service-Ireland, Civil Services, Ireland, Politician, Reform European Market, National Economic and Social Council.
Keywords: National Economic and Social Council; Reform European Market; Politician; Ireland; Civil Service; Civil Service - Ireland